(untitled) (Research, Society and Development, 2022)
The aim of this study was to describe a clinical case report on aesthetic and functional rehabilitation involving retreatment procedures endodontic, fiberglass pin, clinical crown augmentation, periodontal surgery, whitening and total unit crown, emphasizing the importance of multidisciplinary approach. A patient came to the dental clinic of Tiradentes University - UNIT with the main complaint of frequent neglect of the temporary crown of unit 22 and dissatisfaction regarding the coloration of the teeth. For the clinical success of the treatment a multidisciplinary approach was necessary, with endodontic retreatment of unit 22 followed by making a prefabricated fiberglass pin, periodontal surgery for clinical crown augmentation for smile correction, external tooth whitening of the upper and lower arches and making the all-ceramic crown with lithium disilicate of the aforementioned unit. It was possible to conclude that multidisciplinary communication is an important factor for excellent results in complex cases, especially in areas that require greater aesthetic demands, recovering the patient’s self-esteem.